1986
DOI: 10.1002/bit.260280302
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hydrogen gas and butanol production by Clostridium saccharoperbutylacetonicum

Abstract: Two simultaneous fermentations were performed at 26 degrees C with simultaneous inocula using Clostridium saccharoperbutylacetonicum. Fermentation 1 prevented the gas formed by the biomass from escaping the fermentor while 2 allowed the gas formed to escape. Fermentor 1 provided for the production of butanol, acetone, and ethanol, while when the H(2) formed was allowed to escape with fermentor 2, neither butanol nor acetone were produced. Ethanol was also formed in both fermentors and began along with the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Such a phenomenon is similar to that of Jones and co-workers (1982), who reported that VFAs (i.e., acetate and butyrate), but not solvents (i.e., butanol and acetone), are produced by Clostridium acetobutylicum during exponential growth. Obviously, the growth response of hydrogen-producing microorganisms obtained from the chemostat reactor was in general good agreement with that of Clostridium sp.-consuming carbohydrates in normal-batch culture (Afschar et al, 1986;Brosseau et al, 1986;Jones et al, 1982;). As a result, it must be concluded that both influences of pH and HRT in starchhydrogen fermentation corresponded closely to its metabolic control.…”
Section: Effects Of Ph and Hrt On Microorganism Metabolismmentioning
confidence: 52%
See 3 more Smart Citations
“…Such a phenomenon is similar to that of Jones and co-workers (1982), who reported that VFAs (i.e., acetate and butyrate), but not solvents (i.e., butanol and acetone), are produced by Clostridium acetobutylicum during exponential growth. Obviously, the growth response of hydrogen-producing microorganisms obtained from the chemostat reactor was in general good agreement with that of Clostridium sp.-consuming carbohydrates in normal-batch culture (Afschar et al, 1986;Brosseau et al, 1986;Jones et al, 1982;). As a result, it must be concluded that both influences of pH and HRT in starchhydrogen fermentation corresponded closely to its metabolic control.…”
Section: Effects Of Ph and Hrt On Microorganism Metabolismmentioning
confidence: 52%
“…3A, C, D) show that the production trends of hydrogen/VFA were clearly opposite to that of alcohols. This mechanism is remarkably similar to that of Clostridium sp.-consuming carbohydrates, such as glucose and sucrose (Afschar et al, 1986;Brosseau et al, 1986;Jones et al, 1982;). Previous studies (Lay et al, 1999a(Lay et al, , 1999b(Lay et al, , 1999c have demonstrated that the boiling of sludge can readily deactivate hydrogentrophic bacteria and has a great potential to enhance the sludge's clostridial characteristics.…”
Section: Characteristics Of Hydrogen-producing Microorganismsmentioning
confidence: 79%
See 2 more Smart Citations
“…For example, when Clostridium pasteurianum are grown in high glucose concentrations significant quantities of alcohols are produced (Harris et al, 1986). Brosseau et al (1986) also reported that the hydrogen was produced in the cell growth phase, whereas the cells produced butanol at equilibrium. The efficiency of a hydrogen-producing bioprocess depends highly upon optimal control of factors such as the ratio of substrate concentration to biomass concentration.…”
Section: Introductionmentioning
confidence: 96%